Editor's Choice-Progress in the chain of survival and its impact on outcomes of patients admitted to a specialized high-volume cardiac arrest center during the past two decades. Issue 7 (1st November 2016) - Sulzgruber, Patrick; Sterz, Fritz; Schober, Andreas; Uray, Thomas; Van Tulder, Raphael; Hubner, Pia; Wallmüller, Christian; El-Tattan, Diana; Graf, Nikolaus; Ruzicka, Gerhard; Schriefl, Christoph; Zajicek, Andreas; et al.
Abstract: Aim: Cardiac arrest (CA) is still associated with high mortality and morbidity. Data on the changes in management and outcomes over a long period of time are limited. Using data from a single emergency department (ED), we assessed changes over two decades. Methods: In this single-center observational study, we prospectively included 4133 patients receiving cardiopulmonary resuscitation and being admitted to the ED of a tertiary care hospital between January 1992 and December 2012. Results: There was a significant improvement in both 6-month survival rates (+10.8%; p  < 0.001) and favorable neurological outcome (+4.7%; p  < 0.001). While the number of witnessed CA cases decreased (-4.7%; p  < 0.001) the proportion of patients receiving bystander basic life support increased (+8.3%; p  < 0.001). The proportion of patients with initially shockable ECG rhythms remained unchanged, but cardiovascular causes of CA decreased (-9.6%; p  < 0.001). Interestingly, the time from CA until ED admission increased (+0.1 hours; p  = 0.024). The use of percutaneous coronary intervention and therapeutic hypothermia were significantly associated with survival. Conclusions: Outcomes of patients with CA treated at a specialized ED have improved significantly within the last 20 years. Improvements in every link in the chain of survival were noted.